On the Fiftieth Anniversary of the Labour Code - Sanetra, Walerian (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The Labour Code has been on force for fifty years. It was based on a number of assumptions, in particular: universality of regulations, their comprehensiveness, distinctiveness of the labour law system, axiological distinctiveness, ensuring greater rule of law and justice in employment relations, arrangement of conceptual apparatus and conciseness and coherence of statutory regulations. The content of the Code and its formal and legislative side were thoroughly rebuilt as a result of political and socio-economic changes after 1989, and them as a result of Polish accession to the European Union in 2004. At the time of its entry into force in 1975 – compared to other country of so-called socialist camp – the Polish Labour Code was distinguished by its greater technical and legislative quality as well as its systemic and socio-economic adequacy. Twice unsuccessful attempts (2007, 2018) to enact a new Labour Code have been made. Despite dozens of amendments and erosion of its provisions, the Code is still in force and, moreover, in the new EU reality, it is difficult to expect that it will be replaced by new code or that it will be repealed without introducing a new code in its place.